Employee ambidexterity: The influence of entrepreneurial orientation on increasing competitive advantage in the tourism industry - Khusna, Khanifatul; Hari Sukarno; Salma Fauziyyah (Annals of Human Resource Management Research, 2025)
Purpose The aim of this study is to examine how ambidexterity capabilities (exploration and exploitation) and entrepreneurial orientation contribute to competitive advantage in East Java's tourism industry. Methodology/approach: The research was conducted in East Java's tourism sector, involving a survey of 230 tourism managers selected through purposive sampling. The data was analyzed using path analysis with mediation tests and t-tests through SmartPLS to examine the relationships between the study variables. Results/findings: This study found that Entrepreneurial Orientation (EO) enhances both exploratory and exploitative ambidexterity, which promotes innovation and efficiency. Although EO directly enhances competitive advantage, its impact varies across the dimensions of ambidexterity. Exploratory ambidexterity weakens the relationship between EO and competitive advantage, while exploitative ambidexterity strengthens it. This suggests that balancing innovation with execution is key to sustaining success in the market. Conclusions: The research concludes that tourism organizations in East Java should focus on developing ambidexterity exploitation capabilities to maximize the benefits of their entrepreneurial orientation for achieving competitive advantage. The balanced management of external challenges proves more crucial than internal resource management in this context. Limitations: A limitation of the study is its focus on East Java's tourism industry and its use of purposive sampling, which may affect the generalizability of findings to other regions or sectors. Contribution: This study contributes to tourism management literature by empirically testing the ambidexterity-competitive advantage relationship in an underexplored context. The findings provide practical insights for tourism managers on strategically allocating resources between exploration and exploitation activities to enhance their competitive position.